Successful treatment of nonocclusive mesenteric ischemia after aortic valve replacement with continuous arterial alprostadil infusion: A case report. (2017) - Ogi, Kunio; Sanui, Masamitsu; Iizuka, Yusuke; Aomatsu, Akinori; Nakashima, Ikue; Hamamoto, Kohei; Okochi, Tomohisa; Lefor, Alan K.
Highlights: Serum lactate level is a useful clinical marker of nonocclusive mesenteric ischemia. Some patients with NOMI may be unresponsive to continuous arterial infusion of papaverine. Continuous arterial infusion of PGE1 may limit the extent of resection in refractory NOMI. Abstract: Introduction: Nonocclusive mesenteric ischemia (NOMI) after surgery has an extremely poor prognosis with a mortality rate of 30–100%. We report a patient with NOMI following aortic valve replacement who failed to improve despite continuous intra-arterial infusion of papaverine, but was successfully treated with alprostadil (prostaglandin E1 [PGE1]) infusion. Presentation of case: The patient is a 77-year-old man who underwent aortic valve replacement. Due to elevated serum lactate levels five hours after intensive care unit admission, superior mesenteric arteriography was performed, establishing the diagnosis of NOMI. Although continuous intra-arterial infusion of papaverine was begun, lactate levels remained elevated. Repeat angiography and laparotomy revealed extensive ischemic changes of the intestine. The vasodilator was changed to PGE1, which improved arterial spasm. The patient ultimately needed an ileocecal resection, but the extent of the resection was limited with concomitant PGE1 administration. Discussion: In the present patient, although NOMI was unresponsive to appropriate treatment including intra-arterial infusion of papaverine, continuous intra-arterial infusion of PGE1 salvaged most of the intestine. Conclusions: In a patient with recurrent NOMI despite appropriate treatment including intra-arterial infusion of papaverine, continuous intra-arterial infusion of PGE1 may limit the extent of intestinal resection needed. Continuous intra-arterial infusion of PGE1 may be a useful treatment for patients with refractory NOMI.